2020
DOI: 10.1155/2020/1079129
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Alleviates Hepatic Ischemia and Reperfusion Injury by Regulating Glutathione Production and Transformation

Abstract: Inflammation and oxidative stress are pivotal mechanisms for the pathogenesis of ischemia and reperfusion injury (IRI). Vagus nerve stimulation (VNS) may participate in maintaining oxidative homeostasis and response to external stimulus or injury. We investigated whether the in vivo VNS can protect the liver from IRI. In this study, hepatic IRI were induced by ligating the vessels supplying the left and middle lobes of the liver, which underwent 1 h occlusion followed with 24 h reperfusion. VNS was initiated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The liver I/R injury process causes the aggregation and activation of downstream adaptor proteins and signal kinases. 23 The evidence derived from our study suggested that miR-497-5p, MED1/TIMP2 and the NF-κB signaling pathway affect the inflammatory responses in liver I/R injury. Initially, our study suggested that miR-497-5p was highly expressed in liver I/R injury both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 59%
“…The liver I/R injury process causes the aggregation and activation of downstream adaptor proteins and signal kinases. 23 The evidence derived from our study suggested that miR-497-5p, MED1/TIMP2 and the NF-κB signaling pathway affect the inflammatory responses in liver I/R injury. Initially, our study suggested that miR-497-5p was highly expressed in liver I/R injury both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 59%
“…Cui et al ( Cui et al, 2018 ) found that the protection of short-acting opioids against I/R injury in multiple organs, including the liver, acts through the central vagus pathway. Many studies have reported that VNS can alleviate hepatic I/R injury and skeletal muscle I/R injury by inhibiting inflammation and alleviating oxidative stress ( Zhang et al, 2019a ; Zhang et al, 2019b ; Lai et al, 2019 ; Xia et al, 2020 ). Medeiros et al ( Lauz Medeiros et al, 2016 ) found that antioxidants protect against intestinal damage caused by hepatic I/R injury by reducing inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic IR resulted in hepatic injury as proved by increased level of liver enzymes. Hepatic IR causes the disruption of the membrane stability of hepatocytes due to necrosis, cellular damage, and structural changes with release of large quantities of liver enzymes [37][38][39].…”
Section: Discussionmentioning
confidence: 99%